Religious Program Management in Shaping Love-Based Behavior in Students at MAN 1 Pangkalpinang - Muhammad Afrianyah; Abdullah Idi; Febriyanti Febriyanti; Ahmad Zainuri (FKIP - Universitas Riau, 2026)
This study is motivated by the importance of managing religious programs in shaping students’ religious behavior and character within the madrasa environment. The Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) is implemented as an approach to instill values of love, care, discipline, and responsibility in students’ daily lives. This study aims to analyze the management of religious programs in shaping love-based behavior among students at MAN 1 Pangkalpinang from the perspective of Islamic education management and the Love-Based Curriculum (KBC). This research employed a qualitative approach with a case study design. The research subjects involved 5 informants consisting of teachers and students. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and data verification techniques. The results showed that management functions, including planning, organizing, implementation, supervision, and evaluation, had been carried out systematically. Religious programs were implemented through worship habituation, character development, strengthening discipline, and fostering social and environmental awareness. The integration of the five pillars of love in KBC was able to shape students’ religious, disciplined, environmentally caring, and responsible behavior and became a model for developing religious program management in Islamic senior high schools.